Calidad del servicio y su influencia en la satisfacción de los clientes de los hoteles de la ciudad de Portoviejo - Vilela Illescas, Erick Javier (2024)
The objective of this study was to evaluate the quality of service to improve customer satisfaction in hotels in the city of Portoviejo. The type of research used is mixed with a descriptive approach. In the first phase, a diagnosis of the quality of hotel service in the city was carried out, identifying a total of five hotels with a capacity of approximately 400 people. This made it possible to gather updated information on the situation of the hotels through a characterization sheet and interviews, resulting in a strategic analysis through a SWOT matrix. In the second phase, the measurement of service quality variables was carried out using a questionnaire of the HOTELQUAL model that establishes three dimensions of 20 items. Three hundred and eighty-five national and foreign tourists who stayed at the five hotels in Portoviejo were surveyed. Then, the data was analyzed, resulting in 10 variables out of 20 in service deficiency status. Finally, the strategies were structured to address the problems of the previous phase, and nine strategies were designed to improve the quality of the services provided in these hotels.